Literatura infanto-juvenil e suas contribuições no processo de alfabetização: uma análise das dissertações produzidas nos últimos 16 anos no Estado do Amazonas - Lima, Rayane Lima de (Brasil, 2025)
This Course Completion Work (TCC) addresses the contribution of children's literature to the literacy process, emphasizing literary reading and its pedagogical functionality in the classroom. The general objective is to analyze how debates about children's literature in the literacy process have been presented based on dissertations produced in the last 16 years, using the State of Amazonas as the empirical field of data production. To address the topic, the specific objectives are: a) Understand how literature is used in the literacy process in Amazonas, according to the selected dissertation works. b) Describe how dissertations produced in Postgraduate Programs (PPGs) articulate literature and literacy in the context of the State of Amazonas; c) Describe which discussions are presented in relation to the articulation between teacher training and the literacy process, inserting literature into pedagogical practices in Amazonas; d) Identify the conceptions about literacy reported by the selected dissertations. The research is based on a qualitative approach, according to González Rey (2015), and has a theoretical mapping based on Biembengut (2008) for the production of data, as this author helps in the direction of works that seek to understand the productions developed on a theme specific. Five dissertations were selected to compose the analysis of this work. We sought to analyze the literacy processes presented in the selected dissertations, understanding how literature is used in this context, exploring current legislation, such as the BNCC and the DCNs, and how these guide the literacy process. The works analyzed presented concepts about theories that enable the use of literature in the school environment. Based on this, the dissertations that make up the analyzes of this TCC indicate that, in the last 16 years, there have been few works that address the literacy process with a focus on literature. Research on Amazonas presents limited data, and the dissertations that cover these themes, although old, deal with problems that still recur in the school environment. Despite the existence of policies that aim to improve the literacy process, it is clear that, in the current context, this process is still outdated.